2015
DOI: 10.1037/neu0000208
|View full text |Cite
|
Sign up to set email alerts
|

Absence of practice effects in preclinical Alzheimer’s disease.

Abstract: Objective To describe how practice effects influence cognitive trajectories and determine if a reduction in practice effects is a potential marker of Stage 3 preclinical AD. Method Participants included 263 older adults who were cognitively normal at baseline (CDR=0) and returned for an average of 9.5 annual visits. Participants completed standard tests of episodic memory, visuospatial ability, semantic memory, and executive function. Progressors (n=66) converted to CDR>0 with a diagnosis of symptomatic AD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
116
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 51 publications
12
116
0
Order By: Relevance
“…In our clinical study, the ES that we saw for immediate and delay recall compares favorably to ES of ≤0.2 for WMS immediate or delayed recall at week 12 in the placebo‐treated subjects in two trials of Souvenaid in a similar patient population (mild AD, baseline MMSE = 24) 32, 33. Although with the absence of a placebo group our results could reflect practice effect, we think this is unlikely since the learning effects on episodic memory tests that are well recognized in cognitively intact older individuals are less prominent, or absent, in biomarker‐positive early AD 34, 35. The highly correlated relationship between increasing plasma drug concentration of neflamapimod with increasing improvement in immediate/delayed also suggests that there is a true drug treatment effect.…”
Section: Discussionmentioning
confidence: 76%
“…In our clinical study, the ES that we saw for immediate and delay recall compares favorably to ES of ≤0.2 for WMS immediate or delayed recall at week 12 in the placebo‐treated subjects in two trials of Souvenaid in a similar patient population (mild AD, baseline MMSE = 24) 32, 33. Although with the absence of a placebo group our results could reflect practice effect, we think this is unlikely since the learning effects on episodic memory tests that are well recognized in cognitively intact older individuals are less prominent, or absent, in biomarker‐positive early AD 34, 35. The highly correlated relationship between increasing plasma drug concentration of neflamapimod with increasing improvement in immediate/delayed also suggests that there is a true drug treatment effect.…”
Section: Discussionmentioning
confidence: 76%
“…For example, Hassenstab et al (Hassenstab, et al, 2015) found that the magnitude of gain in episodic memory from repeated testing assessed by annual visits was inversely related to progression risk in individuals who were cognitive normal at baseline. We previously showed that individuals who developed incident MCI or dementia showed an initial practice effect in episodic memory followed by declining performance thereafter (Machulda, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Jonaitis et al (Jonaitis et al, 2015) examined practice effects in a middle aged cohort of 594 individuals (mean age at baseline for individuals without a family history of AD was 56.6, those with a family history of AD was 53.30) and found that the group with a family history of AD showed attenuated practice effects on measures of working memory and speed/flexibility. Hassenstab and colleagues (Hassenstab et al, 2015) examined a cohort of 263 cognitively normal older adults (mean age at baseline was 71.74 for cognitively stable participants, 74.67 for Progressors) over a span of approximately 9½ years and found that those who progressed to a CDR > 0 with symptomatic AD showed a reduction in practice effects in episodic memory. These studies lend support for the notion that the lack of practice effects in cognitively asymptomatic individuals may be the first harbinger of future cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have reported an absence of practice effects in MCI on various cognitive measures across various retest intervals (Britt et al, 2011; Cooper, Lacritz, Weiner, Rosenberg, & Cullum, 2004; Darby, Maruff, Collie, & McStephen, 2002; Schrijnemaekers, de Jager, Hogervorst, & Budge, 2006). Conversely, others have reported improvements on repeated testing in these patients (Duff et al, 2007; Mathews et al, 2014; Yan & Dick, 2006), and that patients with MCI who do not show practice effects tend to have worse outcomes than those that do show improvements on retesting (Duff et al, 2011; Hassenstab et al, 2015; Machulda et al, 2013). …”
mentioning
confidence: 90%